Ensoli, Serena - La Rocca, Eugenio. Aurea Roma. Dalla città pagana alla città cristiana. Roma: L' Erma di Bretschneider, 2000, 710 pp. - Hubeñak, Florencio (2002)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina; Argentina